Safer cycling in the urban road environment: study approach and protocols guiding an Australian study - Stevenson, M.; Johnson, M.; Oxley, J.; Meuleners, Lynn; Gabbe, B.; Rose, G. (B M J Group, 2014)
Background: Much of the research into cyclist safety in Australia has focused on behaviour with less focus on the impact of the urban transport environment on cyclist safety. A greater understanding of the urban transport system and the improvements needed to create a safer cycling environment are essential if cyclists are to be safe and increased cycling participation targets are to be achieved. The proposed study will use existing cyclist crash data along with unique cyclist exposure data to develop road infrastructure prototypes that improve cyclists' safety and evaluate the effectiveness of these prototypes in a cycling simulator. Methods and design: This study will be conducted in two Australian cities namely Perth and Melbourne as both cities have policies that strongly advocate cycling. Two methods of data collection will be employed: (1) in-depth crash investigations of injured cyclists; and (2) video footage of cyclist exposure through a naturalistic cycling study of non-injured cyclists. The findings from these two methods will be used to develop new urban road design prototypes which will be tested with a sample of cyclists and motorists in safe environment namely, a cycling simulator and a driving simulator. Discussion: By designing and evaluating safer environments for cyclists, this study will identify solutions that reduce the risk of road trauma and importantly, support this alternative mode of transport and thereby contribute to a reduction in traffic-related emissions and pollution and enhance sustainable economic and social connectivity.